Monocyte Tumor Necrosis Factor-α-Converting Enzyme Catalytic Activity and Substrate Shedding in Sepsis and Noninfectious Systemic Inflammation. - O'Callaghan,DJ; O'Dea,KP; Scott,AJ; Takata,M; Gordon,AC (Critical Care Medicine, 2015)
OBJECTIVES: To determine the effect of severe sepsis on monocyte tumor necrosis factor-α-converting enzyme baseline and inducible activity profiles. DESIGN: Observational clinical study. SETTING: Mixed surgical/medical teaching hospital ICU. PATIENTS: Sixteen patients with severe sepsis, 15 healthy volunteers, and eight critically ill patients with noninfectious systemic inflammatory response syndrome. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Monocyte expression of human leukocyte antigen-D-related peptide, sol-tumor necrosis factor production, tumor necrosis factor-α-converting enzyme expression and catalytic activity, tumor necrosis factor receptor 1 and 2 expression, and shedding at 48-hour intervals from day 0 to day 4, as well as p38-mitogen activated protein kinase expression. Compared with healthy volunteers, both sepsis and systemic inflammatory response syndrome patients' monocytes expressed reduced levels of human leukocyte antigen-D-related peptide and released less sol-tumor necrosis factor on in vitro lipopolysaccharide stimulation, consistent with the term monocyte deactivation. However, patients with sepsis had substantially elevated levels of basal tumor necrosis factor-α-converting enzyme activity that were refractory to lipopolysaccharide stimulation and this was accompanied by similar changes in p38-mitogen activated protein kinase signaling. In patients with systemic inflammatory response syndrome, monocyte basal tumor necrosis factor-α-converting enzyme, and its induction by lipopolysaccharide, appeared similar to healthy controls. Changes in basal tumor necrosis factor-α-converting enzyme activity at day 0 for sepsis patients correlated with Acute Physiology and Chronic Health Evaluation II score and the attenuated tumor necrosis factor-α-converting enzyme response to lipopolysaccharide was associated with increased mortality. Similar changes in monocyte tumor necrosis factor-α-converting enz